Chinese Society of Gynecological Endocrinology affiliated to the International Society of Gynecological Endocrinology Guideline for Ovarian Tissue Cryopreservation and Transplantation. (2nd December 2018) - Ruan, Xiangyan
Abstract: In order to promote the standard application of ovarian tissue cryopreservation in China, and to provide effective scientific medical services of fertility preservation for patients, the First Chinese Guideline of Ovarian Tissue Cryopreservation and Transplantation is established according to the agreements between gynecologists, embryologists, oncologists, pediatricians, breast oncologists, hematologists, and experts on Traditional Chinese Medicine (TCM), based on already successful treated cases within Beijing Obstetrics and Gynecology Hospital, Capital Medical University, China, and based on already existing international guidelines on fertility preservation including important publications in this field. The guideline includes selection criteria, evaluation, and indications; SOPs of ovarian tissue removal, transportation, preparation, freezing, and thawing; approaches of ovarian tissue transplantation and follow-up; practical recommendations for ovarian tissue cryopreservation and transplantation including recommendations of the diseases where this method could be available, and treatment of menopausal symptoms during the peri-transplantation period (time between cryopreservation and retransplantation). The aim of this guideline was to be scientific, practical, and operable. 摘要：: 为提高中国卵巢组织冻存的标准化应用, 以及为患者提供有效科学的生育力保护医疗服务, 根据首都医科大学附属北京妇产医院成功案例, 并汇总现有的生育力保护领域的国际指南和重要出版物, 通过妇产科、生殖科、肿瘤科、儿科、乳腺科、血液科、中医科等专家的充分讨论, 制定首部中国卵巢组织冻存移植指南。本指南包括筛选标准、评估指征；卵巢组织取材、转运、复苏、卵巢组织移植方法和随访的标准化操作流程；卵巢组织冻存移植的实践推荐, 包括此技术的适用疾病推荐, 以及移植前后更年期症状的治疗。本指南聚焦于 科学性、实用性以及可操作性。